Determinant attributes influencing retail pharmacy selection by Malaysian consumers / Abdul Farid Abdul Kareem - Abdul Kareem, Abdul Farid (2013)
The Malaysian retail pharmacy market is experiencing strong growth and changing drastically. However, very little research is available to understand the store image attributes driving purchasing behavior in retail pharmacy. Consumers prefer to shop at retail stores with attributes that satisfy their needs. Understanding the antecedents that drive purchase, satisfaction and repatronage influence important decisions related to the retail marketing mix. The objectives of this study are to (1) understand consumer preference on retail formats offering medicines and health related goods and services in Malaysia, (2) investigate the impact of store image attributes on store choice, and (3) examine the relationship between store image attributes and store satisfaction; and the relationship between store satisfaction and store loyalty. A survey was conducted on 246 retail pharmacy customers in 4 key states in Malaysia to understand the store image attributes and its relationship to store satisfaction in the Malaysian retail pharmacy store. The nine attributes proposed by Lindquist (1974-1975) was tested in this survey using a six-page self-administered questionnaire. The results showed that the consumers surveyed ranked retail pharmacy as their primary retail type for health related products and services while hypermarket and traditional grocery store came in next. The study established that store image attributes positively effected store satisfaction; and store satisfaction in-turn positively effected store loyalty. Three of the nine store image attributes were shown to have an effect on store satisfaction in Malaysia. The result of this study sheds some light on the complexities of store image formation and outlines further research to understand purchasing behavior in Malaysia.